Personal and academic narratives of exiled and displaced scholars - Kmak Magdalena; Farzamfar Mehrnoosh (Routledge, 2022)
Refugee scholars and intellectuals reflect more often compared to other refugees on their displacement as a condition of political or cultural significance. While some are silent about their experiences or refuse to be called refugees or ‘exiled intellectuals’, others recognise the impact of exile or migration experience on their academic work and thought. With reference to the biographies and archival materials of some scholars exiled from Nazi Germany in 1930s and 1940s, we analyse interviews with four currently displaced legal scholars. Despite the difference in circumstances of exile and refuge, common threads emerge from the research materials. These common threads encompass both personal and academic narratives connected to three elements: (1) the condition of exile and the experience of asylum and refuge policies and procedures; (2) development of the scholar’s academic career and scholarly identity; (3) the issues related to human rights, justice, and the need to act in relation to the scholar’s home country. In this chapter, we discuss the emotional aspects of scholarly work, contributing to a growing body of research on both migrant emotions and academic emotions, in particular emotions in legal academia.
Refugees and Knowledge Production: Europe’s Past and Present